2021
DOI: 10.1101/2021.03.10.434820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bi-directional flow of the funny current (If) during the pacemaking cycle in murine sinoatrial node myocytes

Abstract: Sinoatrial node myocytes (SAMs) act as cardiac pacemaker cells by firing spontaneous action potentials (APs) that initiate each heartbeat. The funny current, If, is critical for the generation of these spontaneous APs; however, its precise role during the pacemaking cycle remains unresolved. We used the AP-clamp technique to quantify If during the cardiac cycle in mouse SAMs. We found that If is persistently active throughout the sinoatrial AP, with surprisingly little voltage-dependent gating. As a consequ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…We simulated the murine SAM AP using the published model developed by Kharche et al [ 34 ], updated to more closely recapitulate our experimental datasets. First, we adjusted the formulation of several ionic currents based on our measurements of I CaL [ 35 ], transient and steady-state outward K + currents (I to and I sus ) [ 36 ], and I f [ 37 ] ( Figure 1 A). Then, we applied a global optimization method [ 38 ] to scale selected model parameters ( Table A1 ) to match measured AP characteristics ( Figure 1 B and Table A2 ) [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We simulated the murine SAM AP using the published model developed by Kharche et al [ 34 ], updated to more closely recapitulate our experimental datasets. First, we adjusted the formulation of several ionic currents based on our measurements of I CaL [ 35 ], transient and steady-state outward K + currents (I to and I sus ) [ 36 ], and I f [ 37 ] ( Figure 1 A). Then, we applied a global optimization method [ 38 ] to scale selected model parameters ( Table A1 ) to match measured AP characteristics ( Figure 1 B and Table A2 ) [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data previously collected by the Proenza laboratory [ 35 , 36 , 37 , 39 ] were used to constrain model reparameterization. Briefly, SAMs were isolated from 2–3 months old male C58BL/6 J mice [ 73 , 74 ], and membrane currents and spontaneous APs were recorded at 35 °C in whole-cell and amphotericin perforated patch configurations, respectively [ 35 , 36 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, until now this concept could not be validated in vivo and therefore remained controversially discussed. Moreover, it has been shown that, especially in the mouse SAN, the gating kinetics of HCN channels are much too slow to open and close the channels during successive action potentials, because the very high sinus rhythm and thus the firing rate of murine SAN pacemaker cells are markedly faster than the channel kinetics ( Fenske et al, 2011 , 2020 ; Hennis et al, 2021 ; Peters et al, 2021 ). As a result, HCN4-mediated current will manifest mainly as a nearly time-independent but bidirectionally flowing background current during the pacing cycle ( Figure 2E ), strongly arguing against a role for HCN4 in adjusting the slope of SDD and altering HR.…”
Section: Does Camp-dependent Regulation Of Hcn4 Mediate the Chronotropic Effect?mentioning
confidence: 99%